2017
DOI: 10.1007/s10815-017-0995-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of live birth rates and perinatal outcomes between cryopreserved oocytes and cryopreserved embryos

Abstract: In our study, live birth rates and perinatal outcomes were not significantly different in patients after oocyte and embryo cryopreservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 31 publications
(29 reference statements)
1
9
0
1
Order By: Relevance
“…The time in storage does not seem to affect the cycle outcome for either cryopreservation technique [ 29 , 90 , 91 ]. A retrospective cohort study [ 92 ] comparing outcomes of more than a thousand babies born from vitrified oocytes versus fresh oocytes suggested that oocyte vitrification does not increase adverse obstetric and perinatal outcomes nor congenital anomalies and complimented similar findings from previous smaller studies [ 28 , 93 , 94 ]. Of note, the proportion of female offspring was significantly higher in the vitrification group (53.8% vs. 47.4%).…”
Section: A Word Of Cautionsupporting
confidence: 61%
“…The time in storage does not seem to affect the cycle outcome for either cryopreservation technique [ 29 , 90 , 91 ]. A retrospective cohort study [ 92 ] comparing outcomes of more than a thousand babies born from vitrified oocytes versus fresh oocytes suggested that oocyte vitrification does not increase adverse obstetric and perinatal outcomes nor congenital anomalies and complimented similar findings from previous smaller studies [ 28 , 93 , 94 ]. Of note, the proportion of female offspring was significantly higher in the vitrification group (53.8% vs. 47.4%).…”
Section: A Word Of Cautionsupporting
confidence: 61%
“…In women without a partner, outcomes of oocyte cryopreservation have improved significantly over the past decade such that they are now not significantly different compared to those of embryo cryopreservation. 101 Donor oocytes may also be a treatment option for women whose ovaries were either removed due to malignancy or who do not have sufficient oocytes for use with in-vitro fertilization but who desire to carry a pregnancy derived from her partner's sperm.…”
Section: Additional Techniques For Fertility Preservation In Eoc Patimentioning
confidence: 99%
“…Las tasas similares de fertilización, implantación, embarazo, aborto y número de recién nacidos vivos producto de oocitos frescos vs. vitrificados sugiere no sólo la integridad morfológica, sino también la funcional. 36,37 La vitrificación ha mostrado tasas de embarazos superiores a la técnica de enfriamiento lento así como mayor supervivencia de oocitos congelados, por lo que actualmente se considera la técnica de elección. 18,38 Un metaanálisis que incluyó 14 estudios controlados, aleatorizados que compararon ambas técnicas sugiere que la vitrificación puede ser más efectiva causando menos daño a folículos primordiales así www.medigraphic.org.mx como menor tasa de rupturas en el ADN y mejor preservación de células estromales.…”
Section: Criopreservación De Oocitosunclassified